2015
DOI: 10.1177/1938640015593078
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Health Literacy in Patients With Foot and Ankle Injuries

Abstract: Prognostic, Level IV study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Previous research into the health literacy skills and abilities of traumatically injured people is limited. Rosenbaum et al conducted a survey of US patients presenting with foot and ankle injuries to an emergency department showed a high prevalence of low health literacy [ 41 ]. Shahan et al also found trauma patients surveyed in a US outpatient department to have poor recall and knowledge of their injury and operations [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research into the health literacy skills and abilities of traumatically injured people is limited. Rosenbaum et al conducted a survey of US patients presenting with foot and ankle injuries to an emergency department showed a high prevalence of low health literacy [ 41 ]. Shahan et al also found trauma patients surveyed in a US outpatient department to have poor recall and knowledge of their injury and operations [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,5,8,9,11 Patient understanding of postoperative protocols and instructions is both crucial and particularly challenging in foot and ankle surgery. 12 Complex anatomy may be difficult for patients to comprehend, and postoperative restrictions (necessary to protect wounds, arthrodesis, tendon transfers, and soft tissue repairs) can be difficult to follow. This holds particularly true for the Lapidus procedure, which requires patients to protect their wounds, take medication to prevent deep vein thrombosis, remain nonweightbearing while allowing for bony healing, follow progressive weightbearing instructions, and perform range of motion exercises among other tasks required for a good recovery.…”
Section: Introductionmentioning
confidence: 99%
“…LiMP scores below 6 are reported to indicate limited musculoskeletal HL and “…scores of ≥6 can effectively rule out both limited musculoskeletal literacy and general health literacy” (p. 191) [14]. The LiMP has been used to evaluate the musculoskeletal HL of those with carpal tunnel syndrome [15], foot and ankle complaints [16], those presenting to an emergency department [14, 17] and an orthopaedic outpatients clinic [18]. It has a Flesch-Kincaid grade level of 4.2 (able to be read by those with a 4th grade education or above) [17].…”
Section: Introductionmentioning
confidence: 99%